Asian Development Bank investment in Greater Mekong Sub-region (GMS) Cross-Border Livestock Health and Value Chains Improvement Project - CGIAR Research Program on Climate Change, Agriculture and Food Security (2021)
Up to ~USD185 million invested in Greater Mekong Sub-region (GMS) Cross-Border Livestock Health and Value Chains Improvement Project and $30 million loan (approved) for sustainable rangeland of Mongolian herders.